Optimizing the Performance of the NTB Information Commission in Resolving Public Information Disputes in the Digital Era - muh ihsan; Dimas Kurniawan; M. Basisal Abid; Abdul Hafiz (Yayasan Siti Widhatul Faeha, 2026)
This article examines the optimization of the performance of the NTB Information Commission (KI NTB) in resolving public information disputes in the digital era. The study aims to analyze the dispute resolution process, identify existing challenges, and explore opportunities for institutional improvement using a qualitative descriptive method through observation, interviews, and document analysis during a student internship at the University of Muhammadiyah Mataram from January 22 to March 13, 2026. The findings show that KI NTB has implemented a systematic dispute resolution mechanism consisting of application intake, mediation, and non-litigation adjudication, while maintaining the principles of transparency and accountability in accordance with Law No. 14/2008. However, several obstacles remain, including limited human resources, low public awareness, resistance from certain public bodies, and the underutilization of digital technology. In conclusion, KI NTB has demonstrated a significant role in safeguarding citizens’ rights to information and promoting accountable governance, although further optimization is still required. The implications of this study indicate that service digitalization through online registration and e-archiving, capacity building, and more intensive public outreach can strengthen KI NTB’s effectiveness in delivering fair and efficient dispute resolution services.